PHOTOELECTRIC MONITORING OF ACTIVE CLOSE BINARIES - Pribulla, T.; Chochol, D.; Parimucha, S.; Rovithis, P.; Rovithis-Livaniou, H.; Tremko, J. (Одеські астрономічні публікації, 2017)
The results of the long-term UBV R photoelectric monitoring of active close binaries XY UMa, RT And, VW Cep and SW Lac are presented. The orbital period changes are discussed including light-time effect and apparent changes caused by the surface activity. The presence and effects of other components to the studied close binaries are stressed. Clean light curves are constructed and resulting photometric elements are used to determine the absolute parameters of the systems.